The Relationship of Conformity and Memory - Rogayeh Mohammadi, Gholam Hossein Javanmard (Journal of Educational, Health and Community Psychology, 2015)
AbstractÂ Some theorists believe that the brain was evolved under the influence of the community and for the community. So it seems that social function has priority on pure cognitive in the brain. The purpose of this research was to study the relationship between conformity and general memory. The current study is a descriptive-correlational research by using prediction (regression) method. For doing this, 167 students were selected via the multistage cluster method from Bonab and Tabriz Payam Noor universities. For gathering data, the Conformity L-72 Test and general memoryQuestionnaire (PRMQ) were used. The data were analyzed by using Pearsonâs Correlation test and Liner Regression methods. According to the results, the predictive role of conformity for errors in the general memory was confirmed (P<0/01). So that conformity explained 46% of general memory errorsvariance.Based on these results, it seems that social and cognitive functions of the brain are linked together to meet common goals.Keywords: Conformity, General Memory, Social Brain, Cognition